2016
DOI: 10.1002/2015jc011314
|View full text |Cite
|
Sign up to set email alerts
|

Focusing of baroclinic tidal energy in a canyon

Abstract: Strong three‐dimensional focusing of internal tidal energy in the Petite Sole Canyon in the Celtic Sea is analyzed using observational data and numerical modeling. In a deep layer (500–800 m) in the center of the canyon, shear variance was elevated by an order of magnitude. Corresponding large vertical oscillations of deep isotherms and a local maximum of horizontal velocity were replicated numerically using the MITgcm. The elevated internal tidal activity in the deep part of the canyon is explained in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Internal tides and turbulent mixing processes in the wider Celtic Sea and Bay of Biscay region have been previously investigated (e.g., New, 1988;Green et al, 2008;Sharples et al, 2009;Hopkins et al, 2014), but it is clear from high-resolution numerical modelling studies (Vlasenko et al, 2014;Vlasenko and Stashchuk, 2015) that the internal tide field is highly heterogeneous, three-dimensional, and shaped by local bathymetry. Specifically, three-dimensional focusing of internal tide energy within Petite Sole Canyon (part of the wider Whittard Canyon system) has been observed and modelled by Vlasenko et al (2016). A broad understanding of internal tide dynamics within Whittard Canyon will help the extrapolation of results along the highly corrugated Celtic Sea continental slope and to dendritic canyons worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Internal tides and turbulent mixing processes in the wider Celtic Sea and Bay of Biscay region have been previously investigated (e.g., New, 1988;Green et al, 2008;Sharples et al, 2009;Hopkins et al, 2014), but it is clear from high-resolution numerical modelling studies (Vlasenko et al, 2014;Vlasenko and Stashchuk, 2015) that the internal tide field is highly heterogeneous, three-dimensional, and shaped by local bathymetry. Specifically, three-dimensional focusing of internal tide energy within Petite Sole Canyon (part of the wider Whittard Canyon system) has been observed and modelled by Vlasenko et al (2016). A broad understanding of internal tide dynamics within Whittard Canyon will help the extrapolation of results along the highly corrugated Celtic Sea continental slope and to dendritic canyons worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…These are the necessary conditions for baroclinic tidal beam generation (Vlasenko et al, ). These beams propagate from the bank periphery to its center focusing tidal energy over the top, similar to the mechanism of tidal energy focusing in canyons (Vlasenko et al, ). This mechanism resembles the effect of focusing in optical lenses.…”
Section: Discussionmentioning
confidence: 85%
“…On the 24 June 2012, a transect of 4 CTD profiles (Figure ) was sampled for nutrients along the axis of the Petite Sole canyon [ Vlasenko et al ., ] adjacent to the canyons A and B in this study. Linear regressions suggested that the variance of the profiles of nitrate + nitrite (N+N), silicate (Si) and phosphate (P) was well explained by the potential density with mean R 2 of 0.96 for N+N, 0.82 for Si and 0.91 for P (p<0.001 for all three regressions).…”
Section: Discussion and Summarymentioning
confidence: 94%
“…They incise the continental margins of all ocean basins and are known hotspots of enhanced deep‐sea sediment and water flux [ Savoye et al ., ], dense water cascades [ Canals et al ., ], benthic biomass [ Duineveld et al ., ] and fishing activity. The complex, irregular topography of the canyons can lead to internal wave generation [ Kunze et al ., ], focusing of internal wave energy [ Vlasenko et al ., ], enhanced diapycnal mixing [ Carter and Gregg , ], and localized up and downwelling [ Allen and Durrieu de Madron , ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation